Analisis Model Spasial Kondisi Lahan Daerah Aliran Sungai (DAS): Mendukung Pengambilan Keputusan Berkelanjutan di DAS Paguyaman, Indonesia - Waode, Faridawaty; Fitryane Lihawa; Hasim; Dewi Wahyuni K. Baderan; Marike Mahmud (PT. Banjarese Pacific Indonesia, 2024)
The Paguyaman watershed in Gorontalo is crucial for life, but it faces land degradation and erosion. This study evaluates land conditions using satellite imagery and spatial data. Results indicate that 58.73% of the area is in moderate condition, while 27.4% is in poor or very poor condition. Recommendations include reforestation with local species and integrated farming systems to improve soil fertility. Regular monitoring using remote sensing technology is proposed for the early detection of vegetation changes. Collaboration between the government, community, and researchers is essential to achieving sustainable watershed management.